Breast milk: friend or foe? - Shawkat, Emma (BMJ Publishing Group, 2011)
Anaphylaxis can occur secondary to breastfeeding. The authors present a case of a 30-year-old woman who complained of chest tightness, shortness of breath and a rash on the third day postpartum. She was treated for anaphylaxis and her symptoms resolved. Because she had taken tramadol prior to this event, a drug reaction was initially suspected. However, she experienced further episodes related to breastfeeding, despite stopping tramadol. Effective control of her symptoms was achieved with regular antihistamines, enabling her to continue breastfeeding. Antihistamines were interrupted after 8 weeks at which point lactation (in hospital) was once again associated with anaphylaxis. The diagnosis of breastfeeding induced anaphylaxis was made. There are six previously reported cases of breastfeeding induced anaphylaxis. The authors describe the second case of breastfeeding anaphylaxis extending beyond the neonatal period, controlled with antihistamines.